Menuju Model Authentic Digital Leadership: Kajian Sosiologis Kepemimpinan Otentik dalam Transformasi Digital - Bahzar, Moh (Universitas Tribhuwana Tunggadewi, 2025)
Digital leadership is needed in the digital transformation process currently underway to oversee rapid change and use of technology in various sectors of life such as trade, education, health, communications or government. This research is important for studying the sociology of authentic leadership in the digital era. This research uses a library research method sourced from writings, books, journals and research results. The results of Leadership research, which lays down the concepts and practices of how a leader mobilizes his or her resources towards a set goal, are very important in prioritizing aspects of humanism, which makes each person meaningful in that effort. The sincerity and sincerity of a leader in carrying out his leadership role selflessly will create strong motivation in his subordinates to move together towards achieving that goal. A good organizational culture can be created along with the good performance displayed by each person. Towards future leaders, universities need to seriously participate in building mechanisms for the birth of authentic leaders who are digitally literate. Kepemimpinan digital diperlukan dalam proses transformasi digital yang tengah berjalan saat ini untuk mengawal perubahan dan pemanfaatan teknologi dengan cepat di berbagai sektor kehidupan seperti perdagangan, pendidikan, kesehatan, komunikasi, atau pemerintahan. Penelitian ini penting untuk mengkaji sosiologi kepemimpinan otentik di era digital. Penelitian ini menggunakan metode tinjauan pustaka (library research) yang bersumber dari tulisan, buku, jurnal serta hasil penelitian. Hasil penelitian Kepemimpinan yang di dalamnya meletakkan konsep dan praktik bagaimana seorang pemimpin ke dalam menggerakkan sumber daya yang dimiliki menuju tujuan yang ditetapkan sangat penting mengedepankan aspek humanisme, yang membuat setiap orang bermakna dalam upaya itu. Ketulusan dan kesungguhan seorang pemimpin menjalankan peran kepemimpinannya tanpe pamrih akan dapat menimbulkan motivasi yang kuat pada bawahannya untuk bergerak bersama ke arah pencapaian tujuan itu. Budaya organisasi yang baik akan dapat diciptakan seiring dengan kinerja baik yang ditampilkan setiap orang. Menuju pemimpin masa depan, perguruan tinggi perlu secara serius turut membangun mekanisme kelahiran pemimpin-pemimpin otentik yang melek digital.